2015
DOI: 10.1681/asn.2015050515
|View full text |Cite
|
Sign up to set email alerts
|

Macula Densa Nitric Oxide Synthase 1β Protects against Salt-Sensitive Hypertension

Abstract: Nitric oxide (NO) is an important negative modulator of tubuloglomerular feedback responsiveness. We recently found that macula densa expresses a-, b-, and g-splice variants of neuronal nitric oxide synthase 1 (NOS1), and NOS1b expression in the macula densa increases on a high-salt diet. This study tested whether upregulation of NOS1b expression in the macula densa affects sodium excretion and saltsensitive hypertension by decreasing tubuloglomerular feedback responsiveness. Expression levels of NOS1b mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
110
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(117 citation statements)
references
References 50 publications
7
110
0
Order By: Relevance
“…In this report, Lu et al 12 extend the aforementioned study by testing the hypothesis that nitric oxide synthase 1b (NOS1b) may be the salt-sensitive isoform of NOS1 in the MD that modulates tubuloglomerular feedback response, promotes sodium excretion, and protects against the development of salt-sensitive hypertension. To test this hypothesis, Lu et al 12 deleted all of the NOS1 splice variants specifically from the MD of C57Bl/6 mice.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…In this report, Lu et al 12 extend the aforementioned study by testing the hypothesis that nitric oxide synthase 1b (NOS1b) may be the salt-sensitive isoform of NOS1 in the MD that modulates tubuloglomerular feedback response, promotes sodium excretion, and protects against the development of salt-sensitive hypertension. To test this hypothesis, Lu et al 12 deleted all of the NOS1 splice variants specifically from the MD of C57Bl/6 mice.…”
mentioning
confidence: 87%
“…12,16 Lu et al 12 show that nitric oxide generation by the MD is not affected in NOS1KO mice generated by deletion of NOS1 exon 1 16 and that the BP of these mice is not affected by a high-salt diet. 12 Genome-wide association studies have identified genes that influence only 2% of BP variability and have not identified genes that influence the salt sensitivity of BP. Only a few genes have been found to be associated with salt-sensitive hypertension using candidate gene association studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, no studies have specifically targeted NOS2 within the nephron; while this isoform may prove to play a role within the nephron in blood pressure (BP) control, its low baseline activity and marked induction under pathologic states have made it empirically a less attractive target for examining the role of NOS isoforms in physiological states. Knockout of NOS1 specifically in the macula densa7 increased the hypertensive response to a high‐salt diet, while CD‐specific NOS1 knockout (KO) mice had salt‐sensitive hypertension and an impaired natriuretic response 3. In contrast, CD‐specific deletion of NOS3 did not affect urinary salt excretion and blood pressure in response to high salt intake 8.…”
Section: Introductionmentioning
confidence: 99%